Difference Based on Student Self Esteem Parenting Parents - Efni Ningsih Putri; Riska Ahmad (Universitas Negeri Padang, 2019)
This study aims to: (1) describe student self esteem, (2) describe parenting style, (3) describe differences in student self esteem based on parenting. This type of research is quantitative with a comparative descriptive approach. The population of this study was 481 Adabiah 1 Padang High School students, sampling using the Stratified Random Sampling technique, and obtained a sample of 218 students. The instrument used was a questionnaire in the form of a Likert scale. The data obtained were analyzed using percentage techniques and to see the difference between two variables, namely using variance analysis (Anava). The research findings show that: (1) students 'self esteem is in the high category, (2) parenting is in the high category, (3) there is a significant difference between students' self esteem based on parenting, where there is a sig value. As small as 0.013 of 0.05, there is a significant difference between student self esteem based on parenting. To determine which self-esteem is higher by looking at the mean value. The mean value of self-esteem authoritarian parenting is 70.16, self-esteem of democratic parenting is 75.28, and self-esteem of permissive parenting is 74.35. Then it can be concluded that self esteem with democratic parenting is higher than authoritarian and permissive parenting.